Walking on Hot Coals: A Phenomenological Study on Dealing with Temptations in the Seminary - Genesis Naparan; Mike R. Canoy; Foelan Degie Mahinay; Jan Elbe Villaflor (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
The seminary life for Catholic seminarians includes aspects of their human, spiritual, academic, and pastoral formation. While staying in the seminary, they may encounter different kinds of temptations that can hinder them from pursuing their priestly vocations. This research explored the diverse temptations diocesan priests experienced when they were still seminarians. This study then explored the diverse ways of managing these temptations for the research participants. Using the transcendental phenomenology design, the researchers interviewed ten priests to explore their experiences on how they dealt with their experienced temptations. After the data analysis, six themes surfaced on temptations: family-related temptations, sexuality, deviation from the seminary structure, the temptation to isolate from the community, the envy of life outside the seminary, and doing things inconsistent with the priestly vocation. To cope with their temptation, they employed strategies such as: cultivating self-discipline, prayer, and reflection, being faithful to the mandates of the priestly vocation, living in the seminary formation process, and adjusting to community life. Thus, the research participants completed their seminary formation and were ordained as Roman Catholic priests.